The Role of Green Accounting and Sustainability Reporting on Corporate Performance - Purwanto, Medi Tri; Ariyanto, Rudi (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2026)
Corporate green accounting and sustainability reporting play significant roles in enhancing corporate performance by integrating environmental costs and sustainability practices into financial frameworks. Meta-analytical evidence shows a positive impact of green accounting on firm performance, especially when environmental costs are explicitly measured, although country-specific factors do not significantly alter this relationship. Environmental sustainability acts as a crucial mediator between green accounting and corporate performance, reinforcing the importance of sustainable practices in improving company outcomes. Green accounting also improves the quality of sustainability reports, which enhances corporate accountability and environmental disclosure, although its direct effect on company value may vary across sectors. The adoption of environmentally based accounting information systems further supports transparency and long-term risk reduction in sustainability reporting. Additionally, integrating green accounting with corporate social responsibility and carbon performance positively influences environmental and financial performance, highlighting the strategic value of sustainability integration for economic and reputational benefits. Overall, green accounting and sustainability reporting contribute to better corporate performance by promoting environmental responsibility and improving stakeholder trust.